Asymmetry in sprinting: An insight into sub‐10 and sub‐11 s men and women sprinters. (2nd November 2021) - Bissas, Athanassios; Walker, Josh; Paradisis, Giorgos P.; Hanley, Brian; Tucker, Catherine B.; Jongerius, Nils; Thomas, Aaron; Merlino, Stéphane; Vazel, Pierre‐Jean; Girard, Olivier
Abstract : We assessed sprint mechanical asymmetry in world‐class competitors and evaluated whether inter‐limb sex‐based differences in sprinting mechanics exist. The eight finalists in the men's and women's 100 m events at the 2017 IAAF World Championships were studied. Five high‐speed cameras (150 Hz) were used to capture two consecutive steps of the whole body between 47.0 m and 55.5 m from the start, while four additional cameras (250 Hz) focussed on the lower extremities. A total of 33 spatio‐temporal, touchdown and toe‐off joint angles, and horizontal and vertical foot velocity parameters were extracted through three‐dimensional analysis. Group mean asymmetry scores were assessed using the symmetry angle (SA) where scores of 0% and 100% represent perfect symmetry and perfect asymmetry, respectively. Although considered generally low (SA <3% for 22 out of 33 parameters), the magnitude of mechanical asymmetry varied widely between sprinters of the same sex. However, there was no mean SA scores difference between men and women for any stride mechanical parameters (all p ≥ 0.064). Asymmetry scores were inconsistent between parameters and phases (touchdown vs toe‐off instants), and sprinting mechanics were generally not related to asymmetry magnitudes. In summary, low to moderate asymmetry is a natural phenomenon in elite sprinting. Asymmetry was inconsistent between parameters and competitors during near maximum velocity running, yet mean values for a given parameter generally did not differ between sexes. Sprinters' performances were not related to their SA scores.